A process-based evaluation of biases in extratropical stratosphere–troposphere coupling in subseasonal forecast systems - C. I. Garfinkel; Z. D. Lawrence; Z. D. Lawrence; A. H. Butler; E. Dunn-Sigouin; E. Dunn-Sigouin; I. Statnaia; A. Y. Karpechko; G. Koren; M. Abalos; B. Ayarzagüena; D. Barriopedro; et al. (Weather and Climate Dynamics)
Two-way coupling between the stratosphere and troposphere is recognized as an important source of subseasonal-to-seasonal (S2S) predictability and can open windows of opportunity for improved forecasts. Model biases can, however, lead to a poor representation of such coupling processes; drifts in a model's circulation related to model biases, resolution, and parameterizations have the potential to feed back on the circulation and affect stratosphere–troposphere coupling. We introduce a set of diagnostics using readily available data that can be used to reveal these biases and then apply these diagnostics to 22 S2S forecast systems.